2022
DOI: 10.2337/db21-1056
|View full text |Cite
|
Sign up to set email alerts
|

Serum Metabolomics of Incident Diabetes and Glycemic Changes in a Population With High Diabetes Burden: The Hispanic Community Health Study/Study of Latinos

Abstract: Metabolomic signatures of incident diabetes remain largely unclear for US Hispanics/Latinos, a group with high diabetes burden. We evaluated the associations of 624 known serum metabolites (measured by a global, untargeted approach) with incident diabetes in a subsample (n = 2010) of the Hispanic Community Health Study/Study of Latinos without diabetes and cardiovascular disease at baseline (2008-2011). On the basis of the significant metabolites associated with incident diabetes, metabolite modules were detec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…We found that the biosynthesis of valine, leucine and isoleucine belonging to branched chain amino acids (BCAAs), and of phenylalanine, tyrosine and tryptophan belonging to aromatic amino acids (AAAs) was enriched in PDR group, compared with HC group. Increasing evidence reported that BCAAs and AAAs were predictors of occurrence and development of T2D [63][64][65] , which was consist with previous study. Of note, more data pointed that arginine biosynthesis, lysine degradation, histidine and D-ornithine catabolism were enriched in PDR group.…”
Section: Correlations Of the Gut Microbiota With Metabolicsupporting
confidence: 88%
“…We found that the biosynthesis of valine, leucine and isoleucine belonging to branched chain amino acids (BCAAs), and of phenylalanine, tyrosine and tryptophan belonging to aromatic amino acids (AAAs) was enriched in PDR group, compared with HC group. Increasing evidence reported that BCAAs and AAAs were predictors of occurrence and development of T2D [63][64][65] , which was consist with previous study. Of note, more data pointed that arginine biosynthesis, lysine degradation, histidine and D-ornithine catabolism were enriched in PDR group.…”
Section: Correlations Of the Gut Microbiota With Metabolicsupporting
confidence: 88%
“…Finally, we discovered that U.S. nativity related metabolites were collectively associated with representative clinical traits reflecting blood glycemic and lipid profiles, liver function, kidney function, and lung function, to a greater extent than metabolites unrelated to U.S. nativity. Additionally, U.S. nativity related metabolites were collectively overlapped with these metabolites associated with representative common diseases that are prevalent among Hispanics/Latinos in the U.S. Hispanics/Latinos in the U.S. have a high burden of multiple chronic diseases [31,48,49], and prior studies have attempted to pinpoint one or multiple causal factors [13,50,51]. However, our study suggests that a systemic metabolomic shift in metabolic patterns, resulting from the adoption of U.S. lifestyle due to multiple risk factors, significantly contributes to this multifaceted disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic traits, including body mass index, waist-hip ratio, systolic blood pressure, diastolic blood pressure, triglycerides, high-density lipoprotein cholesterol, fasting glucose, after 2-hour glucose, HbA1c, and homeostatic model assessment for insulin resistance, were measured following standardized methods and protocols. 17,18…”
Section: Methodsmentioning
confidence: 99%
“…T2D cases were identified if participants met at least one of the following criteria 17 : fasting glucose ≥7.0 mmol/L (126 mg/dL); after 2-hour glucose ≥11.1 mmol/L (200 mg/dL); HbA1c ≥6.5%; or self-reported antidiabetic medication use. Participants free of diabetes at baseline who were identified as having T2D during the follow-up visits were deemed to be incident T2D.…”
Section: Ascertainment Of T2d and Metabolic Traitsmentioning
confidence: 99%